Plasmon-mediated photocatalytic activity of wet-chemically prepared ZnO nanowire arrays. Issue 11 (21st March 2015) - Dao, Thang Duy; Han, Gui; Arai, Nono; Nabatame, Toshihide; Wada, Yoshiki; Hoang, Chung Vu; Aono, Masakazu; Nagao, Tadaaki
<x xml:space="preserve">Abstract</x> Relation among (1) photocatalytic activity (2) nano-scale electromagnetic field distribution and (3) hot electron injection of metal loaded ZnO wires was elucidated.